2009
DOI: 10.4314/eamj.v85i10.9664
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality And Safety Of <i>Rastrineobola Argentea</i> Retailed In Kisumu Town Markets, Kenya

Abstract: Objective: To investigate faecal contamination and safety of Rastrineobola argentea sold in retail markets in Kisumu town. Design: This was a repeated cross sectional study and based on random sampling. Setting: Kisumu city, targeting six markets; Oile, Jubilee, Kibuye, Kondele, Nyalenda and Manyatta. Results: A total of 60 fish samples were analysed. All the fish were found to be contaminated with E. coli, and in addition 6.67% of the fish products tested positive for Salmonella. Shigella was absent in all sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
4
2
2
Order By: Relevance
“…These findings of antimicrobial susceptibility are in agreement with data from previous studies, which found that resistance to aminoglycosides, β -lactamase, and penicillin is common among E. coli isolates from food of animal origin [ 47 49 ]. However, the resistance frequency in E. coli isolated in the present study was low when compared to other studies, where a resistance of 58% and 42% in raw fish samples from Kenya and Vietnam, respectively, was observed [ 48 , 50 ]. Mussel samples from Niterói (Brazilian Southeastern oceanic region) showed 29% resistance to at least one antimicrobial [ 31 ], and strains isolated from mussels from the Guanabara Bay, Rio de Janeiro, showed 40% to 85% resistance to tested antimicrobials [ 51 ], indicating the intense presence of domestic and industrial effluents.…”
Section: Discussioncontrasting
confidence: 91%
“…These findings of antimicrobial susceptibility are in agreement with data from previous studies, which found that resistance to aminoglycosides, β -lactamase, and penicillin is common among E. coli isolates from food of animal origin [ 47 49 ]. However, the resistance frequency in E. coli isolated in the present study was low when compared to other studies, where a resistance of 58% and 42% in raw fish samples from Kenya and Vietnam, respectively, was observed [ 48 , 50 ]. Mussel samples from Niterói (Brazilian Southeastern oceanic region) showed 29% resistance to at least one antimicrobial [ 31 ], and strains isolated from mussels from the Guanabara Bay, Rio de Janeiro, showed 40% to 85% resistance to tested antimicrobials [ 51 ], indicating the intense presence of domestic and industrial effluents.…”
Section: Discussioncontrasting
confidence: 91%
“…is is in contrast to the results obtained by Kibret and Abera [39], where erythromycin and tetracycline were highly resistant to E. coli isolates at 89.4 and 72.6%, respectively. e high prevalence of resistance to tetracycline, ampicillin, and cotrimoxazole in E. coli in the region has also been reported by Sifuna et al [40], in which E. coli demonstrated resistance mostly to ampicillin and tetracycline. According to Sifuna et al [40], the resistance pattern reported in their study can also be linked to the use of these drugs in veterinary practice and lead to resistance in humans.…”
Section: Discussionsupporting
confidence: 59%
“…The antibiogram of all isolates revealed high degree of sensitivity to Chloramphenicol (95.34%) and gentamicin (93.02%) while high frequency of resistance were observed to ampicillin (67.44%) and streptomycin (32.35%). Results revealed that 67.44 per cent of the isolates showed resistance to ampicillin and such a high percent of resistance among the isolates is in agreement with the findings of Ogbonna et al, (2008), Sifuna et al, (2008), Bolarinwa et al, (2011) and Sanyal et al, (2011) but in contrast to this Barbosa (2014) reported all isolates were sensitivity to ampicillin. Higher frequency of resistance to streptomycin (32.35%) was observed during present study.…”
Section: Resultssupporting
confidence: 87%